Caproic Acid-Producing Bacteria in Chinese Baijiu Brewing - Yuan, Siqi; Jin, Ziyang; Ali, Ayaz; Wang, Chengjun; Liu, Jun (Frontiers in Microbiology, 2022)
Caproic acid bacteria are the main microorganisms that synthesize caproic acid in Chinese Baijiu. This article reviews several common caproic acid bacteria, combs the pathways of caproic acid biosynthesis, describes the role of caproic acid bacteria in co-culture with other microorganisms, and introduces the application of caproic acid bacteria in the Baijiu industry. Our paper provides new ideas for the study of caproic acid bacteria in brewing of Baijiu.